Lessors' Accounting and Residual Values: Comdisco, Barron's, and GAAP. - Powers, Marian; Revsine, Lawrence (The Accounting Review, 1989)
ABSTRACT: Financial reporting of lessors' transactions is a controversial area for several masons: (1) lessors' accounting alternatives (e.g., operating vs. sales-type lease methods) usually generate large financial statement differences; (2) many of the parameters required to implement lessors' accounting choices (e.g., residual value estimates) are "soft" and, therefore, difficult to verify; (3) little is known about the sensitivity of income disclosures to errors in these parameter estimates; and (4) lessors' rules are still evolving and, therefore, are somewhat ill-defined. Using a highly critical Barron's article regarding Comdisco, Inc. as a starting point, this paper analyzes aspects of these masons for controversy, especially (3) and (4). Specifically, Barron's argued that Comdisco's accounting for residual values and other leasing Income recognition procedures were flawed. Using Comdisco's financial reports as a benchmark, we analyze elements of lessors' accounting and evaluate competing reporting options. We then examine the sensitivity of income numbers to residual value estimation errors using a simulation approach. The parameters for the simulation are derived from Comdisco's recent disclosures. The simulation results and analysis are used as a basis for recommending changes in lessors' financial disclosures and income determination.